An Investigation of Pressure Profiles and Wearer Comfort During Walking With a Transtibial Hydrocast Socket. (March 2019) - Laing, Sheridan; Lythgo, Noel; Lavranos, Jim; Lee, Peter Vee Sin
Abstract : Objective: The aims of the study were to conduct an investigation of the transtibial hydrocast socket interface pressures during walking and to explore potential relationships between pressures experienced and resultant wearer comfort. Design: In this cross-sectional study, pressure data at the limb and hydrocast socket interface during walking were collected from 16 users of hydrocast sockets. The pressures at this interface were described by location, magnitude, and duration for all participants and were compared between the most and least comfortable participants. Results: High pressures were found about the bony prominences of the residual limb, especially the tibial crest of the anterior distal region. Factors identified as potentially causing discomfort ( P < 0.1, d > 0.80) were high peak pressures at the anterior proximal region and longer durations of submaximal loading at the lateral proximal region and the anterior and medial distal regions. High pressure variability at the anterior proximal region may also contribute to discomfort ( P = 0.106, d = 0.88). Conclusions: The hydrocast socket interface pressures have been described for a cohort of users. A number of differences were found in the pressure profiles of the most and least comfortable participants. These differences suggest trends between the identified pressure parameters and resultant wearer comfort. Future studies should confirm these exploratory results. Abstract : Supplemental digital content is available in the text.